PENGARUH KOMUNIKASI ORGANISASI DAN KEYAKINAN DIRI TERHADAP PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DASAR NEGERI DI KABUPATEN HUMBANG HASUNDUTAN SUMATERA UTARA - Marina Letara Nababan (Jurnal Dinamika Pendidikan, 2020)
The objective of this research is to understand comprehensively the effect of organizational communication and self-efficacy on the decision making of the principals in Primary Schools District Humbang Hasundutan Sumatera Utara.The research was conducted by a survey method with the causal study and 69 samples by simple random sampling has been selected by Taro Yamane technique. The data have been analysised by applying path analysis. The data analysis and interpretation indicates that (1) organizational communication has positive influence on decision making, (2) self-efficacy has positive influence on decision making, (3) organizational communication has positive influence on self-efficacy. Keywords: decision making, organizational communication, self-efficacy